Alarming Antibiotic Resistance of Lactobacilli Isolated from Probiotic Preparations and Dietary Supplements - Elizaveta Anisimova; Islamiya Gorokhova; Guzel Karimullina; Dina Yarullina (MDPI AG, 2022)
In this study, we screened eight commercially available brands of Lactobacillus-containing probiotic preparations and dietary supplements for resistance towards commonly administered antibiotics of different classes. According to disc diffusion results, most of the isolates were resistant to vancomycin and susceptible to penicillin-type antibiotics (ampicillin and amoxicillin), carbapenems (imipenem, meropenem, and ertapenem), and inhibitors of protein synthesis (chloramphenicol, erythromycin, tetracycline, clarithromycin, and linezolid). However, based on minimum inhibitory concentration (MIC) values, six strains were reconsidered as resistant to tetracycline. All tested lactobacilli were resistant towards amikacin, ciprofloxacin, and norfloxacin. Resistance to cephalosporins was highly variable and decreased in the following order: ceftazidime/cefepime, ceftriaxone, cefotaxime, cefazolin, and cefoperazone. PCR screening for antibiotic resistance determinants in probiotic lactobacilli revealed a wide occurrence of vancomycin resistance gene vanX, ciprofloxacin resistance gene parC, and extended-spectrum β-lactamase gene blaTEM. We also detected the tetK gene for tetracycline resistance in one isolate. Additionally, we identified discrepancies between the claims of the manufacturers and the identified species composition, as well as the enumerated amount of viable bacteria, for several products. The results of this study raise concerns about the safety of lactobacilli for human consumption as probiotics, as they may act as reservoirs of transferable antibiotic resistance genes.